International tax planning and fixed investment - Sorbe, Stéphane (OECD Publishing, 2017)
This paper assesses how international tax planning affects real business investment by multinationals. Earlier studies have shown that corporate taxes reduce business investment. This paper shows that tax planning multinationals are less sensitive to corporate taxes than other firms in their investment decisions. This is presumably because tax planning multinationals do not face the full tax burden associated with their investments, since they shift part of the resulting profits to lower-tax rate countries. On average across industries, a 5 percentage point corporate tax rate increase is found to reduce investment by 5% in the long term. In industries with a strong presence of multinationals with profit-shifting opportunities, this effect is halved. These results obtained with industry-level data are confirmed by a firm-level analysis. Consistently with these results, the investment of tax planning multinationals is found to be more sensitive to taxes when strong rules against tax planning are in place
Keywords: Finance and Investment; Taxation; Economics